(untitled) (Trabalho & Educação, 2016)
This article presents results of a research on the technical Nursing course at Federal Institute of Northern Minas Gerais (IFNMG) – Campus Januária/MG. The data were collected quantitatively from the Research Centre for Education “Technical Secondary Education of the Federal Network of Technological Education of Minas Gerais: Organization of IFETs, Policies for Teaching Work, Continue / Evasion and Transition for Students of Higher Education and Work.” Qualitatively , it was investigated by semi-structured interviews, technicals of the administrative area, teachers and course coordinators in research concerning their conceptions, arguments and interpretations relating to dropout. The theoretical reference revolved on the topics: the context of the technical professional education in health and their relationships with work and professional qualification; school dropout and public politics for professional education. The results indicate some convergence between the views of respondents and the responses of dropout students, when analyzing the causes of dropout in some cases - as the relationship with the work of dropouts, difficulty of transport and mobility - and some differences - with respect to non-identification of dropouts with the chosen course. ___ Este artigo apresenta resultados de uma pesquisa sobre o curso técnico de nível médio em Enfermagem do Instituto Federal do Norte de Minas Gerais (IFNMG) – Campus Januária/MG. Os dados foram coletados quantitativamente, a partir da pesquisa do Observatório da Educação “Educação Técnica de Nível Médio da Rede Federal de Educação Profissional e Tecnológica de Minas Gerais: Organização dos IFETs, Políticas para o Trabalho Docente, Permanência/Evasão de Estudantes e Transição para o Ensino Superior e para o Trabalho”. Qualitativamente, investigaram-se, por entrevista semiestruturada, técnicos da área administrativa, professores e coordenadores do curso em investigação quanto às suas concepções, argumentações e interpretações relativamente ao tema de evasão. O referencial teórico versou sobre os temas: o contexto da educação profissional técnica em saúde e evasão escolar. Os resultados apontam para algumas convergências entre a opinião dos entrevistados e as respostas dos alunos evadidos, quando se analisam as causas de evasão, em alguns casos – quanto à relação com o trabalho dos evadidos, dificuldade de transporte e mobilidade –, bem como algumas divergências – com relação à não identificação dos evadidos com o curso escolhido.